MAKNA FILOSOFIS NILAI-NILAI SILA KE-EMPAT PANCASILA DALAM SISTEM DEMOKRASI DI INDONESIA - Yusdiyanto Yusdiyanto (Universitas Lampung, 2016)
Indonesia is a nation that has a philosophy of Pancasila, therefore, any values in the principles of Pancasila should be applied in the life of the nation. As principles number 4th Pancasila mention